Onychomycosis: A Comprehensive Review of Epidemiology, Diagnosis, and Emerging Therapeutic Strategies - Mansi Chandrakant Godse,; Neha N.Kadam, (Asian Journal of Pharmaceutical Research and Development, 2025)
Onychomycosis is a prevalent fungal infection that affects the nail unit and accounts for over half of all nail-related disorders worldwide. It is mainly caused by dermatophyte species such as Trichophyton rubrum and T. mentagrophytes, although non-dermatophyte molds like Aspergillus and Fusarium, as well as yeasts such as Candida, can also contribute. The infection causes nail discoloration, thickening, brittleness, and discomfort, often leading to a noticeable decline in quality of life. Its occurrence increases with age and is more common among people with diabetes, peripheral vascular disease, compromised immunity, or those undergoing hemodialysis. Accurate diagnosis depends on proper nail specimen collection and confirmation through laboratory techniques such as microscopy, culture, or advanced molecular tools like PCR and immunoassays, which offer greater precision than traditional methods. Treatment involves systemic antifungal agents—such as terbinafine, itraconazole, and fluconazole—or topical formulations like ciclopirox, amorolfine, efinaconazole, and tavaborole. However, oral antifungals can cause liver toxicity and drug interactions, while topical therapies often have limited nail penetration. To address these challenges, novel drug delivery systems such as antifungal nail lacquers have been developed. Econazole nitrate-based lacquers containing film-forming agents, plasticizers, and permeation enhancers improve nail permeability and sustain drug release. Innovative options like iontophoresis, photodynamic therapy, and laser-assisted delivery further enhance effectiveness. Despite progress, recurrence and reinfection are frequent due to residual fungal spores and environmental exposure. Therefore, long-term success depends on patient education, consistent treatment adherence, and preventive practices such as maintaining nail hygiene and using antifungal prophylaxis.